2014
DOI: 10.1039/c4nr04216f
|View full text |Cite
|
Sign up to set email alerts
|

Highly integrated synthesis of heterogeneous nanostructures on nanowire heater array

Abstract: We have proposed a new method for the multiplexed synthesis of heterogeneous nanostructures using a top-down fabricated nanowire heater array. Hydrothermally synthesized nanostructures can be grown only on the heated nanowire through nanoscale temperature control using a Joule heated nanowire. We have demonstrated the selective synthesis of zinc oxide (ZnO) nanowires and copper oxide (CuO) nanostructures, as well as their surface modification with noble metal nanoparticles, using a nanowire heater array. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In our previous study, we reported a localized hydrothermal synthesis method for ZnO nanowires, CuO nanospikes, and TiO 2 nanotubes (NTs). When an electrical voltage is applied across the prefabricated microheaters submerged in the liquid precursor, the temperature rise around the localized Joule-heated region induces a hydrothermal reaction of the precursor chemicals. Also, as convective heat transfer followed by convective mass transfer of the precursor is generated, fresh precursors are continuously supplied to the reaction area where the endothermal reaction continues a selective synthesis of nanomaterials.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our previous study, we reported a localized hydrothermal synthesis method for ZnO nanowires, CuO nanospikes, and TiO 2 nanotubes (NTs). When an electrical voltage is applied across the prefabricated microheaters submerged in the liquid precursor, the temperature rise around the localized Joule-heated region induces a hydrothermal reaction of the precursor chemicals. Also, as convective heat transfer followed by convective mass transfer of the precursor is generated, fresh precursors are continuously supplied to the reaction area where the endothermal reaction continues a selective synthesis of nanomaterials.…”
Section: Introductionsupporting
confidence: 85%
“…[8][9][10][11][12][13] When an electrical voltage is applied across the pre-fabricated microheaters submerged in the liquid precursor, the temperature rise around localized Joule-heated region induces a hydrothermal reaction of precursor chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Seed patterns can be created by the photoreduction of sensitive Ag salts, [137] and the reactivity of an electroless Ag plating bath can be restricted so strongly (using AgNO 3 as the metal source, no alkaline reagents, and citrate as ligand, adsorbate, and rather weak reducer) that metallization only proceeds via plasmon‐mediated reduction on Au seeds, which can be spatially controlled with photomasks [106] . Localized heating, which has been implemented, e. g ., in the patterned growth of oxide nanostructures, [152] represents an interesting option for electroless plating, albeit the decomposition tendency of overheated plating baths has to be considered.…”
Section: Nanomaterials Synthesismentioning
confidence: 99%
“…Furthermore, a transparent Joule heater with a parallel-oriented long Au NW array does not need percolation of NWs; this trait is different from conventional Joule heaters based on short NWs, so high-temperature annealing and waste of materials for connection among dispersed NWs are unnecessary (Figure e). Ag paste pads were used for electrical contact, and the exothermic properties from the heater were observed using an infrared thermometer.…”
Section: Resultsmentioning
confidence: 99%